Effect of Molecular Weight of Tilapia (Oreochromis Niloticus) Skin Collagen Peptide Fractions on Zinc-Chelating Capacity and Bioaccessibility of the Zinc-Peptide Fractions Complexes in Vitro Digestion - Lei Chen; Xuanri Shen; Guanghua Xia (Applied Sciences, 2020)
To investigate the effect of the molecular weight of tilapia skin collagen peptide fractions on their zinc chelation capacity and the bioaccessibility of their zinc complexes, we evaluated the zinc-chelating ability of different molecular weight peptide, the solubility, and the stability of the complexes during simulated in vitro digestion. Low molecular weight peptide (P1) exhibited a higher zinc-chelating ability, which can be attributed to the variety of metal chelate amino acid residues. The highest solubility and the lowest release of zinc during peptic digestion for the P1-zinc complex and the zinc binding to P1 were retained at approximately 50% after peptic-pancreatic digestion. Fourier transform infrared spectroscopy indicated the primary involvement of the N-H group in all peptide-zinc complexes. This finding suggests that low molecular weight peptidefraction with strong zinc chelation ability can be used as delivery agents to improve zinc bioaccessibility.